Soil erosion and land management decisions in Bao Lao District, Lam Dong Province, Central Highlands of Vietnam - Le, Du Van (Animo Repository, 2001)
This paper addressed two questions, namely: 1) how do changes in environmental conditions influence land use management decisions of upland farmers, and 2) what are the linkages between environmental changes and land management decisions at different levels? The paper provided empirical evidence to the dynamic link between decisions and natural resources change. Specifically, the study employed some participatory landscape-lifescape appraisal (PLLA) techniques such as key informants interview and secondary data, which consider the interlocking relationships between environmental changes and land management decisions at a landscape scale. In this study the unit of analysis are two communities located in the Bao Loc district in the Central Highlands of Vietnam, which represent agricultural systems in transition. The paper examined the changes of natural resources—with emphasis on soil erosion—and the factors affecting the land management decisions of farmers and local authorities. Initial results of this research showed that soil erosion in the study sites occurs severely in all crops planted on sloping lands, especially mulberry. All farmers and local authorities are aware about soil erosion occurrence and its damage, but there is little response in their land management decisionmakers. This information could be important input in planning further participatory research activities to address natural resources management.